BETWEEN STIGMA AND SURVIVAL: LIFE NARRATIVES OF VIETNAMESE BRIDES IN CHINA - Pu, Weikang; Elfira, Mina (UI Scholars Hub, 2026)
The phenomenon of cross-border marriages between Vietnamese women and Chinese men is often reduced by mainstream media to simplified stereotypes—depicting them as victims of human trafficking, impoverished women seeking economic escape, or submissive